2009
DOI: 10.1001/archgenpsychiatry.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructural Integrity and Cognitive Function in a General Elderly Population

Abstract: Microstructural integrity of both white matter lesions and normal-appearing white matter is associated with cognitive function, regardless of white matter atrophy and white matter lesion volume. This suggests that measuring white matter integrity has added value beyond macrostructural assessment of white matter changes to study the relation between white matter and cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
244
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(276 citation statements)
references
References 59 publications
26
244
6
Order By: Relevance
“…Although we cannot assume causality, white matter damage is well described in brain injuries, 13,39 and we have previously shown that retired symptomatic NFL athletes with cognitive impairment, depression, or both have compromised white matter integrity compared with either controls or asymptomatic retired NFL players. 30 In our voxelwise analysis, significant clusters within the athlete group were localized around the corpus callosum and its extending projections. The corpus callosum is a dense white matter structure that is structurally vulnerable to jarring or torsional forces that occur in head impacts.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Although we cannot assume causality, white matter damage is well described in brain injuries, 13,39 and we have previously shown that retired symptomatic NFL athletes with cognitive impairment, depression, or both have compromised white matter integrity compared with either controls or asymptomatic retired NFL players. 30 In our voxelwise analysis, significant clusters within the athlete group were localized around the corpus callosum and its extending projections. The corpus callosum is a dense white matter structure that is structurally vulnerable to jarring or torsional forces that occur in head impacts.…”
Section: Discussionmentioning
confidence: 80%
“…Neuropsychological assessment included measures of general cognitive ability, attention, language, memory, visuospatial and executive function, and processing speed 30 prior to neuroimaging. The standard 60 item BNT 1 was used as a measure of visual confrontation naming.…”
Section: Neuropsychological Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies of the role of brain microvascular disease in late-life dementia are going to have to use a direct measure of microvascular disease that captures the pathology more precisely than current neuroimaging. Diffusion tensor imaging may be one strategy to better assess the impact of microvascular disease on brain white matter (23). Diffusion tensor imaging detects changes in normal-appearing white matter and might therefore be more sensitive and specific than white matter hyperintensities for pathology (23).…”
mentioning
confidence: 99%